“YouTube Killed the MTV Star” : did Hip-Hop music videos become the blueprint for other genres of music videos in the digital age? - Pascoal, João Miguel de Matos (2016)
This dissertation presents a deeper look in to Hip-Hop music videos. Starting with a chronological timeline, where we focus in the most relevant music videos that show an evolution in the genre’s aesthetics throughout the years, we build up to the present decade (from 2010 to the present year of 2015), where we intend to find out how much have Hip-Hop music videos evolved, and what elements from past decades have been incorporated in that same evolution. We will also present an in-depth look on the present decade as far as music videos are concerned, and what impact the digital age has in musical culture. Have audiences’ habits changed? What are the main goals of an artist when making a music video and do they match with the record label’s goals? Has the role of music video changed? By constructing both of these studies, we also intend to answer a question that becomes more and more frequent as we see today’s music videos: did Hip-Hop music videos become the blueprint for other genres of music videos? In a world where things can no longer be presented in “black or white” statements and the internet has brought cultures together in an unprecedented way, exchanging cultural influences and learning from each other, one can argue that Hip-Hop, and particularly Rap music, has had a significant influence in the way we produce music videos nowadays. This dissertation intends to be a reflexion on these questions and we have tried our best to obtain a cohesive conclusion, leaving the door open to a future study regarding the role of aesthetics in directing a music video, and whether or not it plays a role as (or even more) important as the narrative beneath the video.